Using Point-in-Time Homeless Counts to Monitor Mortality Trends Among People Experiencing Homelessness in Los Angeles County, California, 2015‒2019 - Nicholas, Will; Greenwell, Lisa; Henwood, Benjamin F.; Simon, Paul (American journal of public health (1971), 2021)
Objectives. To report trends in mortality rates, mortality rate ratios (MRRs), and causes of death among people experiencing homelessness (PEH) in Los Angeles County, California, by using annual point-in-time homeless counts and to compare findings to published longitudinal cohort studies of homeless mortality. Methods. We enumerated homeless deaths and determined causes by using 2015–2019 medical examiner‒coroner data matched to death certificate data. We estimated midyear homeless population denominators by averaging consecutive January point-in-time homeless counts. We used annual demographic surveys of PEH to estimate age- and gender-adjusted MRRs. We identified comparison studies through a literature review. Results. Mortality rates increased from 2015 to 2019. Drug overdose was the leading cause of death. Mortality was higher among White than among Black and Latino PEH. Compared with the general population, MRRs ranged from 2.8 (95% confidence interval [CI] = 2.7, 3.0) for all causes to 35.1 (95% CI = 31.9, 38.4) for drug overdose. Crude mortality rates and all-cause MRRs from comparison cohort studies were similar to those in the current study. Conclusions. These methods can be adapted by other urban jurisdictions seeking to better understand and reduce mortality in their homeless populations. (Am J Public Health. 2021;111(12):2212–2222. https://doi.org/10.2105/AJPH.2021.306502 )